Social Networking Technologies in Promoting Language Socialization: EFL Teachers' Beliefs - Ali Mohammed Saleh Al-Hamzi; Layli Hamida (PAROLE: Journal of Linguistics and Education, 2021)
Teachers' views influence how they choose pedagogical methods and how they execute teaching practices in the classroom. An investigation of teachers' views regarding the notion of "language socialization" (LS) and how it may be used to enhance pedagogical application via the use of social networking technologies (SNTs) in a Yemeni EFL setting is the subject of this study. In this study, 30 EFL teachers participated in a survey. Five males were interviewed out of the total number of participants. The findings revealed that the vast majority of teachers had good associations with LS as a teaching method and positive reactions to the use of SNTs in the EFL classrooms even though most participants had never used SNTs in their own classrooms. Because of a lack of access to and training in the usage of SNTs, teachers have been prevented from integrating them into their classrooms when teaching English. This suggests that instructors recognize the important functions that SNTs play in improving students’ language learning and socialization but that they lack first-hand experience and training in how to use them in their classrooms effectively. That there is a shortage of provision must be addressed as soon as possible to guarantee that Yemeni English as a foreign language teachers and their students have the chance to engage with new technologies in order to enhance their educational experiences critically.